Process parameters evaluation for direct investment casting - Marwah, O. M. F. (International Journals of Engineering and Sciences Publisher, 2016)
The advancement of the rapid prototyping (RP) technologies evolving toward rapid tooling in producing sacrificial patterns rapidly has profoundly benefits the investment casting (IC) process. Direct expendable pattern fabrication via RP techniques in complex and intricate features significantly reduce the cost when associated with single or low volume production. However inappropriate settings of the RP processes and its variables may cause serious defect in the ceramic shell such as cracking during burning out of the patterns, incomplete collapsibility and poor qualities of end products. By implementing the ANOVA at 95% confidence level to study the relative influence of factors and interactions, result shows that Surface Roughness (SR) and Dimensional Accuracy (DA) drastically affected by input variables within 5 % level of significance. Confirmation runs for all responses were carried out to ensure that the models reliability. The error level for ABS P400 was within reasonable range with less than 19%. It is also found that Visijet SR200 acrylate have better variation below than 14%. This study was conducted in an effort to exploit the application of various RP tand materials in the fabrication of IC patterns by utilizing the RP process parameters in minimizing the errors of responses. Moreover, it is expected that this study will provide valuable information and great assistance to the IC manufacturer in producing precise, low cost and rapid patterns using RP technologies.